The usefulness of the useless (Cultura Económica, 2022)
For several years in Latin America philosophy and the humanities have been disappearing from middle and higher level education. This phenomenon is not strange in a utilitarian and global culture in which technical-practical knowledge prevails over philosophy, history, art or literature. The objective of this essay will be to briefly show that this knowledge, considered useless, is basically the most necessary for full personal (Ordine, 2013; Komar, 2021) and social (Nussbaum, 2010) development. And how certain values of this knowledge such as truth, beauty and goodness are demands of human nature (Komar, 2021).
Keywords: HUMANITIES; LEISURE (FREE TIME); CONTEMPLATION; ACADEMIC INDUSTRY; ARTS; UTILITARIANISM